2016
DOI: 10.1016/j.pediatrneurol.2016.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Nerve Biopsy Diagnostic and Treatment Utility in Tertiary Care Referral

Abstract: Pediatric nerve biopsy provides diagnostic information that frequently alters treatment recommendations. Furthermore, it leads to clinical improvements, especially in inflammatory immune neuropathies. For suspected inherited varieties, genetic testing has the highest diagnostic yield in demyelinating phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…4,5 Unexpected pathologic findings from nerve biopsy can also occur supporting toxic, metabolic, genetic, paraneoplastic, and other idiopathic inflammatory disorders. [6][7][8][9][10] For many of these diagnoses, alternative noninvasive testing exists and can reduce the need for biopsies, including next generation DNA sequencing for diverse genetic causes 11 and comprehensive antibody testing in paraneoplastic and other inflammatory disorders. 10 Although nerve biopsies are not required to make a diagnosis of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) in atypical cases not meeting consensus diagnosis criteria, biopsy findings can aid the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Unexpected pathologic findings from nerve biopsy can also occur supporting toxic, metabolic, genetic, paraneoplastic, and other idiopathic inflammatory disorders. [6][7][8][9][10] For many of these diagnoses, alternative noninvasive testing exists and can reduce the need for biopsies, including next generation DNA sequencing for diverse genetic causes 11 and comprehensive antibody testing in paraneoplastic and other inflammatory disorders. 10 Although nerve biopsies are not required to make a diagnosis of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) in atypical cases not meeting consensus diagnosis criteria, biopsy findings can aid the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The primary indications for ordering nerve biopsies are vasculitis, nerve‐based cancers, amyloidosis, and other inflammatory or immune mediated disorders 4,5 . Unexpected pathologic findings from nerve biopsy can also occur supporting toxic, metabolic, genetic, paraneoplastic, and other idiopathic inflammatory disorders 6–10 . For many of these diagnoses, alternative noninvasive testing exists and can reduce the need for biopsies, including next generation DNA sequencing for diverse genetic causes 11 and comprehensive antibody testing in paraneoplastic and other inflammatory disorders 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The reported nerve biopsy complication rate was 1% (3). [1] COMMENTARY. This is a well conducted and important study looking at the role of nerve biopsy in a large series of pediatric patients.…”
mentioning
confidence: 99%
“…Also, as with other studies, we do not have information on the health-care benefits of changed diagnosis or management, such as improvement in patient quality of life, health outcomes, or cost-effectiveness. That said, the numbers of 52% for changed diagnosis and 63% for changed management stand up well against other medical tests for which we have comparable data, for example: (1) utility of echocardiography in detection of mitral valve prolapse (change in diagnosis: 56%; change in treatment: 27%) 9 ; (2) impact of ultrasound on triage of cardiac patients (change in diagnosis: 14%; change in diagnostic plan: 39%; change of medical treatment: 11%) 10 ; (3) utility of fetal ultrasound in screening for aneuploidy (change in counseling regarding prenatal testing: 16.1%) 11 ; (4) utility of pediatric nerve biopsy (changed or refined final diagnosis: 58%; modified treatment: 25%) 12 ; and (5) utility of the electroencephalogram to detect epileptiform abnormalities in patients with a firsttime, non-provoked seizure (test sensitivity and potential to change patient management: 32%-59%). 13 Because a change in management of 63% for EDX, in particular, is higher compared with the other tests thought to be clinically useful, one could argue that the authors erred on the side of caution when they concluded that their data only "seem" to demonstrate clinical utility of EDX.…”
mentioning
confidence: 99%